Technological Change and Workers participation in posts and Telecommunications - International Labour Office (International Labour Office, 1991)
This book stress that that by cutting running costs and improving the quality and range of services provided,new technologies undoubtedly increase the efficiency and effectiveness of service.
Keywords: Technology & Engineering / Engineering (General)